Strengthening Visual Literacy of Language Teachers in Deep Learning Based on Genre-Based Approaches - Yustika Nur Fajriah; Lucky Rahayu Nurjamin; Sinta Dewi; Anggia Nastya (Fakultas Kewirausahaan Universitas Garut, 2026)
This community service program aims to strengthen language teachers’ visual literacy through the implementation of Deep Learning and the Genre-Based Approach (GBA) in teaching narrative texts. Visual literacy is an essential 21st-century skill that enables teachers to critically interpret and integrate visual meanings in multimodal learning. The program involved 20 language teachers—of Sundanese, Indonesian, English, and Arabic—from an Islamic senior high school in Garut. The training was designed through a Digital Storytelling-based simulation emphasizing the four stages of GBA: Building Knowledge of the Field, Modelling of the Text, Joint Construction of the Text, and Independent Construction of the Text. Through a Deep Learning approach, participants developed a deeper understanding of the interconnection between visual and linguistic elements within narrative texts. The results indicate an improvement in teachers’ ability to design multimodal text instruction that is both reflective and contextually meaningful.